2011
DOI: 10.1051/fruits/2011002
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary inventory of fruit fly species (Diptera, Tephritidae) in mango orchards in the Niayes region, Senegal, in 2004

Abstract: --Introduction. Knowledge of tephritid diversity in Senegal was poor before 2004, so PIP-COLEACP and CIRAD, in collaboration with Cérès-DPV, carried out, in 2004, trapping for preliminary detection of fruit flies in six orchards in the Niayes zone. Materials and methods. We selected three mixed mango orchards and three homogeneous mango orchards in this zone. In each orchard, we used three attractants: Terpinyl acetate (Ter), Trimedlure (Tri) and Torula (Tor). Traps were serviced weekly. Results. We captured 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…For mid-and late mango cultivars, Bactrocera invadens caused more than 90% of the damage in both Southern Sudan and Northern Sudan zones [4,27]. In the Sahelian zone (in Senegal-Niayes), Bactrocera invadens was considered to be the principal pest for mangoes during the rainy season [3,10,28]. Previous studies J.-F. Vayssières et al indicated that, in the Forest zone [29,30] and in the Guinean Savanna zone (GuineaKindia [31]), the impact of B. invadens was high during the whole mango season.…”
Section: Discussionmentioning
confidence: 99%
“…For mid-and late mango cultivars, Bactrocera invadens caused more than 90% of the damage in both Southern Sudan and Northern Sudan zones [4,27]. In the Sahelian zone (in Senegal-Niayes), Bactrocera invadens was considered to be the principal pest for mangoes during the rainy season [3,10,28]. Previous studies J.-F. Vayssières et al indicated that, in the Forest zone [29,30] and in the Guinean Savanna zone (GuineaKindia [31]), the impact of B. invadens was high during the whole mango season.…”
Section: Discussionmentioning
confidence: 99%
“…A preliminary inventory of fruit flies in mango orchards was made as part of the joint study by the Comité de Liaison Europe-Afrique-Caraïbes-Pacifique (COLEACP), the Centre de coopération internationale en recherche agronomique pour le développement (CIRAD), the Centre Régional de Recherche en Ecotoxicologie et de Sécurité Environnementale (CERES) and the Direction de la Protection des Végétaux (DPV) that identified 18 species; ten of which were Ceratitis species, six species of Dacus and two of Bactrocera [4]. These last two pest species of great economic importance were identified as Bactrocera cucurbitae (Coquillett) on crops of Cucurbitaceae and Bactrocera invadens Drew Tsuruta & White on fruit tree crops, while the main Ceratitis species were Ceratitis cosyra (Walker) and Ceratitis silvestrii Bezzi [4]. Before B. invadens arrived in Africa, most fruit infestations recorded in West Africa were linked to C. cosyra and C. capitata (Wiedemann) [5,6], but this situation changed completely after.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20]. Regarding mango production, only some studies have outlined system characterizations, which focused primarily on the level of intensification of cropping systems [6,9] and the composition of the orchards [10]. Vayssières et al identified four types of systems in West Africa: the "gatherer production system", "production system under improvement", "more intensive production system" and "large industrialized orchards" [9].…”
Section: Introductionmentioning
confidence: 99%
“…The mango sector in Senegal has high development potential, but an improvement of the mango-based cropping systems is needed to overcome their high production and quality irregularities. Mango-based cropping systems in West African countries are highly varied, from gatherer and pluri-specific orchards to intensive mono-specific orchards [2,6,[8][9][10]. Even though this diversity is generally known, a thorough knowledge of the current systems and their functioning is still lacking for stakeholders' concern with improvement of Senegalese mango production.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation